2016
DOI: 10.1200/jco.2016.34.4_suppl.531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infectious complications on long-term survival following colorectal cancer surgery.

Abstract: 531 Background: Colorectal cancer surgery is associated with significant postoperative morbidity, which may have long-term implications on patient outcomes. We hypothesize that operative complications following surgery for colorectal cancer are associated with increased recurrence and worse survival. Methods: Using a prospectively maintained database, we reviewed patients with colorectal cancer that underwent a curative resection from 2008 to 2015. Patients were categorized by presence of any complication wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systematic review and meta-analysis including 21 studies published between 1965 and 2009 found that anastomotic leak after colorectal cancer surgery is associated with increased local recurrence and cancer-specific mortality but not distant recurrence [30]. Further studies have shown a correlation between postoperative infectious complications and worse overall survival [31][32][33]. A study of 12,075 patients using the Veteran's Affairs cancer registry found that complications were associated with decreased overall survival and that this was primarily driven by infectious complications [32].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis including 21 studies published between 1965 and 2009 found that anastomotic leak after colorectal cancer surgery is associated with increased local recurrence and cancer-specific mortality but not distant recurrence [30]. Further studies have shown a correlation between postoperative infectious complications and worse overall survival [31][32][33]. A study of 12,075 patients using the Veteran's Affairs cancer registry found that complications were associated with decreased overall survival and that this was primarily driven by infectious complications [32].…”
Section: Discussionmentioning
confidence: 99%